Spatially periodic vapor bubble activity during subcooled pool boiling on 1D aluminum alloy micro-fin arrays. (December 2021) - Doran, Brendon; Zhang, Bin; Davani, Shayan; Osafo, Kojo Asiamah; Sutka, Owen; Walker, Abigail; Mueller, Nicholas; Akwaboa, Stephen; Mensah, Patrick; Meng, W.J.; Moore, Arden L.
Highlights: 1D microfin arrays can double heat transfer compared to planar surface. Micropatterning induces periodic upward and downward flow regions. Vapor bubbles observed to migrate out of microchannels to microfin tops. Presence of microfins and/or increasing height may not always improve heat transfer. Abstract: Within the broad field of micro- and nano- scale surface modification to improve pool boiling performance, micro-fin arrays are especially attractive due to their ability to significantly increase wetted surface area with minimal increase in size or weight compared to macroscopic fins. In addition, their regular and repeating geometry enables greater potential for parametric optimization, uniformity, and repeatability as compared to more randomized alternatives. However, the presence of a regular, repeating microscale pattern on a heated surface has previously been shown to create alternating regions of liquid and vapor flow at small length scales which can strongly affect the macroscopic heat transfer performance of the surface. In this work, a combination of pool boiling experiments, high-speed imaging, and numerical modeling were used to investigate vapor bubble behavior and pool boiling heat transfer characteristics from one-dimensional (1D) aluminum alloy micro-fin arrays in the dielectric coolant HFE-7100. Results showed that the presence of 1D micro-fin arrays can significantly enhance pool boiling performance above that of a planar, unpatterned baseline surface but with important and sometimes nonintuitive dependence on micro-fin height. Experimental data indicated that a simple increase in surface area does not necessarily correlate to improved heat transfer performance, while high-speed imaging revealed that the presence of the micro-fins induces a periodic series of upward and downward flow patterns, in addition to distinct vapor bubble migration behavior. These results expand the range of surface types and working fluids for which spatially periodic and distinct liquid/vapor transport pathways created via microscale surface modification have been reported. Graphical abstract: Image, graphical abstract